Ideal and real paradigms: language users, reference works and corpora - Bermel Neil; Knittl Luděk; Alldrick Martin; Nikolaev Alexandre (Cognitive Linguistics)
This article approaches defective and overabundant paradigm cells as an opportunity and pitfall for usage-based linguistics. Through reference to two production tasks involving native speakers of Czech, we show how definitions of these two categories are problematized when multiple forms per context are entrenched, or when pre-emption seems to occur in the absence of entrenchment: in other words, pre-emption occurs via entrenchment of uncertainty. We explain the results by adopting a broader, usage-based perspective. We examine the relationship between frequency (as proxy for exposure) and reference-work information (as proxy for a priori structure) to assess their connection with our experimental results. We assign a role to frequency as helping to form perceptions of “suitable” and “unsuitable” forms, but also note places where non-frequency factors predominate. “Structure” as represented by reference-work recommendations appears to have no significant connection to our experimental results; we discuss reasons for this.